A Comparative Analysis of Dental Caries, Mucosal Dryness, and Salivary Secretion in Pediatric COVID-19 Vaccinated and Unvaccinated Children - Mahesh Shenoy; Mohammed Almarshed; Abdulrahman Said S. Alshamrani; Hussain Ali M. Alzayer; Fares Sami A. Aleshaiwy (Journal of Pharmacy and Bioallied Sciences)
Introduction: There have been isolated reports of oral negative outcomes after COVID-19 immunization in recent months, which calls for more research to determine a potential link to vaccine-induced immune response. Contrasting the salivary secretion, mucosal dryness, and dental caries of children who received the COVID-19 vaccine to those who did not is the goal of the research. Materials and Methods: Around 60 respondents participated in this cross-sectional research. Two groups of 30 folks each were formed. Group A comprised vaccinated kids, whereas Group B comprised unvaccinated kids. Following a thorough history taking of each kid (together with their parents), an intraoral assessment was conducted to look for any indications of caries or mucosal dryness. A quantitative analysis of salivary secretion ensued. The t-test and Chi-square test were used for statistical analysis. Results: Vaccinated kids exhibited decreased salivary secretion and increased dental caries than those who did not, with a P value of less than 0.0001. With a P value equals 0.0002, the vaccinated individuals had greater levels mucosal dryness than the unvaccinated ones. Conclusion: COVID-19 vaccine alters the rate of salivary production, leading to an increase in cases of poor oral health.